Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Konsumen : Studi Kasus : Pembelian Laptop Merk Asus Pada CV. Golden IT Store Banjarmasin - Nida’an Hafia; Husnurrofiq Husnurrofiq; Abdurrahim Abdurrahim (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
The aims of this study are as follows: (1) To examine how products impact customers' purchasing choices at Golden IT Store Banjarmasin. (2) To analyze the impact of pricing on customers' purchasing decisions at Golden IT Store Banjarmasin. (3) To assess how the location influences customers' purchasing decisions at Golden IT Store Banjarmasin. (4) To test the influence of promotions on customers' purchasing decisions at Golden IT Store Banjarmasin. (5) To comprehensively evaluate the collective influence of products, pricing, location, and promotions on customers' purchasing decisions at Golden IT Store Banjarmasin. This research employs a quantitative approach involving the population of CVs. Golden IT Store Banjarmasin, with a sample of 31 respondents. Quantitative data analysis was conducted. The results of this study indicate that: (1) Products significantly impact purchasing decisions at CV. Golden IT Store. (2) Prices significantly impact purchasing decisions at CV. Golden IT Store. (3) The influence of location on purchasing decisions at CV. Golden IT Store is found to be statistically insignificant. (4) The effect of promotions on purchasing decisions at CV. Golden IT Store is relatively insignificant. (5) Collectively, products, promotions, pricing, and location have a substantial impact on purchasing decisions at CV. Golden IT Store.